EFFICIENCY OF THE METHODOLOGY FOR THE DEVELOPMENT OF MOTOR QUALITIES SCHOOLCHILDREN IN SPORTS ACTIVITIES (American Journal of Pedagogical and Educational Research, 2023)
The article presents the results of a pedagogical experiment on the introduction of the author's methodology of accentuated physical education classes with a training focus on the basis of pedagogical testing, annual monitoring of the level of physical status of children aged 6-7 years with their comparative analysis and correlation between analyzed indicators.